2018
DOI: 10.1097/md.0000000000013406
|View full text |Cite
|
Sign up to set email alerts
|

An incidental diagnosis of a giant paraovarian cyst in a female teenager

Abstract: Rationale: Paraovarian cysts (PCs) are cystic tumors that can be encountered between the ovarian hilum and the ovarian fimbria located within the mesosalpinx and broad ligament, being usually diagnosed within the 3rd and 4th decade of life. Patient concerns: We report the case of a 15-year-old female admitted in our clinic for consciousness loss, who was incidentally diagnosed with a giant pelvic cystic at ultrasound. Diagnoses: The magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 30 publications
(40 reference statements)
0
23
0
1
Order By: Relevance
“…[5] Due to the rarity of malignant conditions in pediatric ages, laparoscopy became the first choice even for cystic lesions of up to 25 de cm considered benign, [5] being a viable option even in giant paraovarian cysts. [28] In case of malignant tumors stage IA–IC, when the cyst content is spilled into the peritoneal cavity, adjuvant treatment may be required or even laparotomy. [7] Nevertheless, Seckin et al [29] found strong correlation between the operative diagnosis and the histopathological exam underlining that under the circumstances of a thorough exploration of both tumor and pelvis, laparoscopic approach may be a safe procedure in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Due to the rarity of malignant conditions in pediatric ages, laparoscopy became the first choice even for cystic lesions of up to 25 de cm considered benign, [5] being a viable option even in giant paraovarian cysts. [28] In case of malignant tumors stage IA–IC, when the cyst content is spilled into the peritoneal cavity, adjuvant treatment may be required or even laparotomy. [7] Nevertheless, Seckin et al [29] found strong correlation between the operative diagnosis and the histopathological exam underlining that under the circumstances of a thorough exploration of both tumor and pelvis, laparoscopic approach may be a safe procedure in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Paraovarian cysts (POCs), usually located along the fallopian tube, arise from the mesosalpinx or the broad ligament. They are cystic structures lled with serous uid [2], and regarding their embryological origin, 68% are mesothelial, 30% are embryonic vestiges of paramesonephric (Müllerian) ducts and 2% of mesonephric ducts [1,6]. Müllerian-derived structures are lined by a secretory epithelium, responsible for the cystic dilation; they are also hormonal in uenced, which explains the incidence in postpubertal patients and why they can reach huge sizes [6].…”
Section: Discussionmentioning
confidence: 99%
“…Paraovarian cysts originate in embryologic remnants located in the broad ligament, between the fallopian tube and the ovary. The vestiges may be mesothelial, paramesonephric or mesonephric [1]. POCs represent about 10 % of all adnexal masses, being more common in the third or fourth decade of life [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations